Bibliometric analysis of pre graduate theses at the Faculty of Medicine, Universidad Nacional Mayor de San Marcos - Valle, Rubén (2009)
Introduction: Research is an important area in medical education and should be promoted during the forming years. Thesis is an investigation to acquire a professional title, but there is a decrease in its production as there are other ways of graduation. Objectives: To determine the number of theses, area, specialty and designs utilized. To determine the collaboration between specialists depending on the area and design of investigation. To determine the proportion of theses published in an indexed journal. Design: Bibliometric study. Setting: Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Participants: Theses of Medicine undergraduates. Interventions: Theses elaborated during 1998-2008 were collected from the Library of the Faculty. We read the summaries and in case of doubt, the complete thesis. We analyzed the patterns of frequency through Microsoft Office Excel 2007 and Pajek’s analysis and visualization network. Main outcome measures: Number of theses, areas of research, specialties and methodology design; collaboration between specialties; proportion of theses published in an indexed journal. Results: In 93 theses the clinical and surgical areas were most studied, respectively in 60% and 19%. The design most used was descriptive-transversal and the most studied specialties pediatrics and infectious diseases, that contributed other specialties; 11% of theses were published in an indexed journal. Conclusions: Thesis production was low with irregular trend in the period studied, resulting in 1 of 10 theses published in an indexed journal.